Pertumbuhan Selada Red Romaine pada Intensitas Naungan dan Mulsa Organik Disertai Intensitas Penyiraman Berbeda - Zahwa, Dini Nur Asyifa; Muda, Strayker Ali; Lakitan, Benyamin; Ria, Rofiqoh Purnama; Ramadhani, Fitri (Seminar Nasional Lahan Suboptimal, 2023)
Zahwa, D.N.A., Lakitan, B., Muda, S.A., Ria, R.P., & Ramadhani, F.  (2023). Red romaine lettuce growth on different shading intensities and organic mulching with watering intensities. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 135-144).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Red romaine lettuce (Lactuca sativa L. var. longifolia) is a lettuce variety containing antioxidant, vitamin, and fiber contents that are beneficial in meeting dietary fiber requirements. This vegetable has the potential to be cultivated in suboptimal areas, including urban land. This study was aimed at identifying the impact of several shade intensities and organic mulch with watering intensities on romaine lettuce growth at early vegetative stages. The research followed a split plot design consisting of 2 treatments, namely shade intensity as the main plot (45% shade, 55% shade, and 80% shade) and organic mulch with watering intensities as subplots (without mulch with no intensive watering, organic mulch with no intensive watering, and organic mulch with intensive watering) and repeated 3 times. The results showed that shaded red romaine lettuce (45% shade, 55% shade, and 80% shade) increased growth at early vegetative growth. However, it was not statistically significant. Meanwhile, the application of organic mulch through intensive watering tends to increase shoot and root growth. Differences in shoot and root growth as a result of the treatments applied can also be shown through their visual appearance. Shade and mulch treatments by intensive watering were confirmed to be able to control the microclimate represented through media moisture. The 80% shading and the organic mulch with intensive watering were able to increase media moisture. In conclusion, 80% shading and organic mulch with watering improved red romaine lettuce growth at the early vegetative stage, although recovery to a lower shade is necessary to avoid inhibited root and shoot growth.